Sources of Shakespeare's King Lear - Pavlíčková, Jana; Drábek, Pavel, 1974-; Masarykova univerzita. Katedra anglistiky a amerikanistiky (2006)
The main story of King Lear had been treated many times before Shakespeare used it in his tragedy. He relied upon many works, ranging from the old chronicles to the works of the playwrights in the sixteenth century. However, these sources are too many to be discussed in one thesis. I chose nine works and divided them into three categories, according to their relevance to Shakespeares play. The first group consists of works which provided Shakespeare with the primary story of King Lear or with subplots and important characters. Geoffrey Monmouths Histories, Raphael Holinsheds Chronicles, next Philip Sidneys Arcadia and the anonymous True Chronicle History of King Leir and His Three Daughters belong to this category. The following group includes plays which presents variants of the story. Here, Edmund Spensers Faery Queene and John Higgins Mirror for Magistrates are discussed. The last category contains works which did not provide any fundamental additions and new elements, but were rath
Vedoucí práce: Pavel Drábek
Bakalářská práce (Bc.)--Masarykova univerzita, Filozofická fakulta, 2006
Keywords: bakalářské práce; bachelor's theses